SYNCHRONIZATION OF ESTRUS IN LOCAL AND LARGE WHITE YORKSHIRE SOWS UNDER COASTAL CLIMATIC CONDITIONS - CHAKURKAR, EKNATH B (The Indian Journal of Animal Reproduction, 2023)
To get farrowing in a season when there is demand for the piglets is important from economicpoint of view in pig industry. This can be achieved with other technique of synchronization of estrus. Tostudy the response of local nondescript sows and Large White Yorkshire sows to synchronization, anexperiment invading 72 sows was designed. Prostaglandin F2a analogue (Dinoprost) was used for thesynchronization of estrus in the sows at the dose rate of 7.5 mg/animal and 1 0mg/animal. The resultsindicated that synchronization of estrus was better in group where 7 .5 mg Dinoprost was given.
Keywords: Estrus Synchronization; Sows